The energy question - Foley, Gerald (Penguin Books, 1987)
This survey of our energy needs and resources considers them all from a technical, an environmental and even a political perspective. The revised fourth edition lays particular emphasis on the issues of today: the prospects for nuclear energy after Chernobyl, the availability of oil supplies and the role of renewable resources. A new chapter covers global warming and the threat to the ozone layer...